2021
DOI: 10.3390/cells10123357
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Genes for Killer Cell Immunoglobulin-like Receptors and Their Human Leukocyte Antigen-A/B/C Ligands with Abdominal Aortic Aneurysm

Abstract: Abdominal aortic aneurysm (AAA) is an immune-mediated disease with a genetic component. The multifactorial pathophysiology is not clear and there is still no pharmacotherapy to slow the growth of aneurysms. The signal integration of cell-surface KIRs (killer cell immunoglobulin-like receptors) with HLA (ligands, human leukocyte class I antigen molecules) modulates the activity of natural killer immune cells. The genetic diversity of the KIR/HLA system is associated with the risk of immune disorders. This study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…Many inflammatory cells in the aneurysmal tissue produce cytokines and enzymes promoting ECM degradation, depletion of SMCs, and vessel wall injury and remodeling [ 86 ]. A genome-wide association study in BS identified genes involved in focal adhesion, MAPK signaling, transforming growth factor beta (TGF-β) signaling, ECM-receptor interaction, and complement and coagulation cascades [ 80 , 87 ], suggests their involvement in pathogenesis ( Table 2 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many inflammatory cells in the aneurysmal tissue produce cytokines and enzymes promoting ECM degradation, depletion of SMCs, and vessel wall injury and remodeling [ 86 ]. A genome-wide association study in BS identified genes involved in focal adhesion, MAPK signaling, transforming growth factor beta (TGF-β) signaling, ECM-receptor interaction, and complement and coagulation cascades [ 80 , 87 ], suggests their involvement in pathogenesis ( Table 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…KIR3DL1/DS1 functional polymorphisms are found in BS [ 102 ]. KIR3DL1/DS1 and their HLA-class I ligands are associated with aneurysm formation in abdominal aortic aneurysms (AAA) [ 86 ].…”
Section: Discussionmentioning
confidence: 99%